Robust three-phase state estimation for PV-Integrated unbalanced distribution systems. (15th September 2022) - Song, Shaojian; Xiong, Hao; Lin, Yuzhang; Huang, Manyun; Wei, Zhinong; Fang, Zhi
Highlights: A distribution system state estimation (DSSE) framework for unbalanced distribution systems hosting single-phase and three-phase PV power plants is proposed. The proposed DSSE framework seamlessly fuses measurements from smart inverters and weather stations with conventional measurements from the distribution network, and do not require the deployment of new sensors. The proposed EWLAV algorithm is robust against simultaneous bad data in measurements and control inputs, which is critical to the monitoring of PV power plants whose states are heavily dependent on inverter control signals. Abstract: As the increasing penetration of renewable energy brings uncertainty and fluctuation into the operating conditions of distribution systems, distribution system state estimation (DSSE) needs to track not only the state of the network, but also the state of the renewable energy sources robustly and under unbalanced conditions. Aiming at delivering comprehensive situational awareness of distribution systems hosting solar photovoltaic (PV) power plants, this paper proposed a joint state estimation model for unbalanced distribution systems integrated with single-phase and three-phase PV power plants, as well as an extended weighted least absolute value (EWLAV) estimation algorithm for handling simultaneous measurement errors and control input errors. The proposed state estimation model considers various loss components of single-phase and three-phase power electronic converters, and is applicable to general unbalanced conditions including unbalanced phasing and parameters of distribution lines, PV power plants, and loads. The proposed EWLAV algorithm leverages sparse l 1 optimization principles and can identify and suppress the gross errors in both measurements and converter control inputs. Simulation results show that the developed model can reliably reflect the characteristics of three-phase unbalanced distribution networks and PV plants, and the EWLAV algorithm produces unbiased results under simultaneous measurement errors and control input errors, which conventional estimators such as the weighted least squares (WLS) and weighted least absolute values (WLAV) cannot achieve.